P030 Exploring online forums to understand parents' and families' views about sources of support and resources for managing children's sleep problems in the community and primary care. (19th November 2019) - Hornsey, Samantha; Hill, Catherine; Muller, Ingrid; Stuart, Beth; Everitt, Hazel
Abstract : Introduction: Behavioural insomnia (BI) is the commonest sleep disorder in children (Hill, 2011) and primary care provides opportunity to prevent or address sleep problems early. However, limited research in this area suggests that it is not often discussed in consultations (Honaker and Meltzer, 2016). Parents or carers of children with sleep problems access the internet, for information regarding children's sleep problems (Hatton and Gardani, 2018). To date, there is no published research into online discussion forums exploring parent's perceptions of the management of children's sleep in primary care. This qualitative study aims to explore: What parents express in online forums regarding their concerns and expectations about children's sleep problems. What resources parents are aware of either online, in the community and through primary care to help them manage children's sleep problems. How parents and families perceive that their children's sleep problems are currently addressed during GP consultations in Primary Care. Methods: A qualitative analysis of public posts about children's sleep problems in primary care or the community, posted by parents/carers in online discussion forums. Searches will be conducted in three active online discussion forums using terms such as 'sleep', 'doctor' and 'health visitor'. Data will be collected by viewing and downloading the first 300 relevant discussion threads and analysed based on inductive thematic analysis in Nvivo, by reading and rereading the data, by creating and revising a coding schedule and by refining the emerging themes and subthemes. Results: Data collection is on-going. Results will be presented at the conference. Discussion: This study will provide a valuable insight into parents' and carers' perceptions of the available support for children's sleep problems in primary care and the community. This will help direct future research, to address areas for improvement and develop suitable support tools for Primary Care providers and families.